Survei Keterampilan Futsal Ekstrakurikuler di SMK Telenika Palembang - Apriadi, Rexi; Lubis, Patricia Hotma Minar; Akhbar, M.Taheri (ANTHOR: Education and Learning Journal, 2023)
This study aims to determine how much influence agility training has on the ability to dribble soccer players at the Bhayangkara Youth Club Sungai Rotan, Muaraenim Regency. The problem in this research is whether there is an effect of agility training on the ability to dribble football players at the Bhayangkara Sungai Rotan Youth Club, Muaraenim Regency. This research methodwill use a quantitative descriptive method and the type of research is quasi-experimental in theone-group pretest-protest design category. The sample in this study amounted to 20 people. Thesample is part of the number and characteristics possessed by the population. If the population islarge and the researcher can't study everything in the population, for example, due to limitedfunds, manpower, and time. Data collection techniques in this study were carried out by tests and measurements. This study gave the result that there was an effect of agility training on the ability to dribble the football athletes at the Bhayangkara Sungai Rotan Youth Club resulting in an average dribbling ability of the initial test players was 33.36 seconds, and the average dribbling ability of the final test players is 32.89 seconds. Judging from the increase in dribbling speed for the Bayangkara Sungai Rotan Youth Club players, it is known that agility training has a good effect on the players, it is proven that there is an increase in speed in the average final ability of the Bhayangkara Sungai Rotan Youth Club players.